ChemInform Abstract: Catalytic Stereoselective Conjugate Addition of Oxindole to Electron‐Deficient Alkynes. Issue 28 (21st June 2013) - Jiang, Jun; et al., et al.
Abstract An E/Z‐selective and enantioselective conjugate addition to construct multifunctional olefins is developed.